Ordinary saints: women, work, and faith in Newfoundland - Morgan, Bonnie (McGill-Queen's studies in the history of religion, 2019)
"From their everyday work in kitchens and gardens to the solemn work of laying out the dead, the Anglican women of mid-twentieth-century Conception Bay, Newfoundland, understood and expressed Christianity through their experience as labourers within the family economy. Women's work in the region included outdoor agricultural labour, housekeeping, childbirth, mortuary services, food preparation, caring for the sick, and textile production. Ordinary Saints explores how religious belief shaped the meaning of this work, and how women lived their Christian faith through the work they did. In lived religious practices at home, in church-based voluntary associations, and in the wider community, the Anglican women of Conception Bay constructed a female theological culture characterized by mutuality, negotiation of gender roles, and resistance to male authority, combining feminist consciousness with Christian commitment. Bonnie Morgan brings together evidence from oral interviews, denominational publications, census data, minute books of the Church of England Women's Association, headstone epitaphs, and household art and objects to demonstrate the profound ties between labour and faithfulness: for these rural women, work not only expressed but also shaped belief. Ordinary Saints, with its focus on gender, labour, and lived faithfulness, breaks new ground in the history of religion in Canada."--